Perolehan Hak Guna Bangunan (HGB) Bersumber Dari Tanah Hak Milik Oleh PT. Harfhavi Mega Utama (Studi Di Kantor Notaris/PPAT Suhardi, SH, M.Kn) - Yeven dri (Normative Jurnal Ilmiah Hukum, 2026)
Land issues are a crucial factor influencing development. Land issues arise not from a lack of adequate legislation, nor from a lack of human capacity to implement them, but rather from a lack of understanding and appreciation of the agrarian or land sector. Article 4 of Law Number 5 of 1960 concerning Basic Agrarian Principles states that: "Based on the state's right to control, various types of land rights are determined, which can be granted to and held either individually or jointly with other individuals and legal entities." These granted land rights authorize the individual to use it. Land use must be tailored to the circumstances and nature of the rights, so that it provides benefits for both the welfare and happiness of the people and the state. The land rights referred to are ownership rights, use rights, building rights, use rights, lease rights, land clearing rights, forest product collection rights, other rights not included in the rights mentioned above which will be determined by law as well as temporary rights as mentioned in Article 53 of the UUPA. Currently, land is widely allocated for housing. Such as the government's One Million Houses program through the Ministry of Public Works and Public Housing (PUPR) which encourages housing developers to provide decent housing for the community so that housing developers in areas throughout Indonesia will need sufficient land availability. PT Harfhavi Mega Utama which is domiciled in Agam Regency, West Sumatra Province is a housing developer that needs land for the construction of the Arumi Residence II Housing in Lubuk Basung Village, Lubuk Basung District, Agam Regency, West Sumatra Province. PT Harfhavi Mega Utama can obtain land originating from Building Use Rights (HGB). The acquisition of Building Use Rights (HGB) is stated in Article 36 Paragraph (1) of the UUPA, which states: Those who may have building use rights are: Indonesian citizens and legal entities established under Indonesian law and domiciled in Indonesia.